Truth, Tolerance, Monotheism. Is There a Possibility For an Inter-religious Dialogue? - Зизијулас, Јован Д (Sabornost - The Theological Year-book, 2013)
Is monotheism, by its nature and definition, “a closed world that denies me and forced me to renounce somebody else”? Is it true that the monotheistic view is not responding to my existential questions related to me, to somebody else, or to the world… as… “a freezing cage that within its bars makes fixed every living creative movement”? Answer to this question may not be than positive. It is really so, if someone accepts the notion of monotheism, assumed and described by Adonis. Is it, however, possible to achieve a different sense of monotheism, which would lead to different conclusions and may make acceptable some inter-religious dialogue?